Treatment patterns and economic outcomes in patients with juvenile idiopathic arthritis - Marshall A; Gupta K; Pazirandeh M; Bonafede M; McMorrow D (Dove Medical Press, 2019)
Alexander Marshall,1 Kiran Gupta,1 Michael Pazirandeh,1 Machaon Bonafede,2 Donna McMorrow21Health Economics and Outcomes Research, Bristol-Myers Squibb, Lawrenceville, NJ, USA; 2IBM Watson Health, IBM, Cambridge, MA, USAPurpose: To describe health care resource utilization (HCRU) and costs among patients with juvenile idiopathic arthritis (JIA) compared to patients without JIA and to describe treatment patterns among JIA patients who initiated biologic and non-biologic disease-modifying antirheumatic drugs (DMARDs).Patients and methods: The IBM MarketScan®, Commercial Database was used to identify patients aged 2–17 years with a new JIA diagnosis (index date) and 12 months continuous enrollment pre- and post-diagnosis from 2008 to 2016. JIA patients were matched to non-JIA patients on age, gender, region, and health plan type. Patients with other rheumatic or autoimmune conditions were excluded. Receipt of a biologic and/or non-biologic was evaluated on or after the new JIA diagnosis.Results: A total of 3,815 JIA patients were matched to 11,535 non-JIA patients (mean age 10.0 [SD=4.5], 69% female). Average total costs were greater for JIA patients than non-JIA controls ($18,611 [SD=$42,104; median=$8,189] versus $2,203 [SD=$9,309; median=$649], p<0.001). Outpatient pharmacy costs were 33.6% of the total costs among JIA patients compared to 18.4% among non-JIA patients (p<0.001). The proportion of inpatient cost (11.4% versus 14.3%, p<0.001) and outpatient costs (55% versus 67.4%, p<0.001) of total costs was lower among JIA patients compared to non-JIA patients. Patients with 12 months of continuous enrollment post-treatment initiation (n=2,014) were classified as non-biologic only (n=734), biologic only (n=873), and both biologic and non-biologic (n=407) users. Among biologic and non-biologic users, 41.1% and 56.8% were persistent on their index medication for 12 months. Of patients treated with a biologic only, TNF inhibitors (TNFi) comprised 87.1% of the total treatment costs.Conclusion: JIA is associated with increased costs and utilization in every HCRU category compared to matched non-JIA patients. While JIA-related costs varied by treatment cohort, patients on biologic DMARDs had substantially higher costs than patients on non-biologic DMARDs and fewer than one-half were persistent at 12 months after biologic initiation.Keywords: juvenile arthritis, antirheumatic agent, medication adherence, health expenditures, administrative claims